Trains - Morse, Jenifer Corr. (Woodbridge, CT : Blackbirch Press, 2001)
Provides information on the world's fastest trains, in simple text with illustrations, and includes the Nozomi, the Eurostar, the Ave, and the Inter-city 225.
Includes bibliographical references and index.
5.9.
5.9
3-6
Keywords: Railroads -- Trains -- Juvenile literature; Railroads -- Trains; Railroads